(untitled) (Global Journal of Science Frontier Research, 2023)
The investigation had objective to reproduce on tubetes the species Sporobolus virginicus as plantation material for dune ecosystems benefitted with sand dumpings The variables evaluated were sprouting percentage height number of leaves and number of sprouts Three substrates sand sand humus and worm humus was evaluated In the substrate with more sprouting percentage was evaluated the position of the rhizome segment horizontal vertical and in angle of 45 the angle formed in the cut 90 and 45 the viability at 24 o clock 48 72 and 96 hours from its prospecting and the survival post-transplant The rhizomes planted in humus did not sprout The biggest sprouting percentage with 37 was obtained in the compound by the mixture of sand and humus The horizontal position of the segments of rhizomes in the tubetes reached the biggest values for the evaluated variables and the number of final sprouts duplicated the vegetable established material initially The position forming angle of 45 showed increment in the number of sprouts until the 64 days The angle in the cut of the rhizome did not influenced in the evaluated variables At the 96 hours of having carried out the prospecting the viability of the segments of rhizomes was affected It is possible the reproduction of this species in tubetes with the use of worm humus and sand until the 72 hours of being prospected the vegetable material and with 100 of survival post-transplant